Development of cookies from wheat-yellow/white maize composite blends and their physical and sensory evaluation - Muhammad Adnan; Masood Sadiq Butt; Imran pasha; Muhammad Shahid (PLoS ONE, 2025)
Wheat is a staple food in many countries globally, but it alone cannot meet the dietary demands of the growing population. To address this, there is an increasingly critical need to integrate alternative cereals into diets, enhancing nutritional diversity and reducing reliance on imports. In present study, various composite blends of wheat and maize were developed by taking different proportions of maize flour (10, 20, 30 and 40%) into the wheat flour and analyzed for proximate composition, phytates, minerals and pasting properties. By using these blends, cookies were made and tested for their physical and sensory evaluation. The crude fat, fiber and ash contents were increased significantly as the amount of maize into composite blends increased but insignificant for moisture, protein and NFE contents while reduction in the phytates was observed. The mineral analysis of various flours showed an increase in the calcium, magnesium, potassium and sodium while decrease in zinc contents. The pasting behaviour of wheat maize composite blends showed a significant decrease in their viscosities as the quantity of maize flour increased. The physical/textural parameters revealed a reduction in diameter and thickness whereas increase in hardness as the amount of maize supplementation increased which had diminishing affect at higher concentrations. It was observed that addition of maize flour into the wheat flour in the development of cookies at higher concentration negatively affected the sensorial attributes.